Medial Plantar Artery Flap for Soft Tissue Coverage of Heel Defect: A Case Report - Wijaya, Ramadhani Hengki; Fachrizal, Achmad ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: Numerous flap options exist for providing soft tissue coverage for defects on the heel region. This study presents a case where a bone-exposed wound on the left heel region was successfully reconstructed using a medial plantar artery flap. Case Report: A 16-year-old girl presented with a necrotic wound on the left heel region with calcaneus, malleolus, and talus fractures following trans-ankle external fixation on her left leg. After debridement and necrotomy, the wound revealed exposed calcaneus and implant. A medial plantar artery flap was dissected, preserving its vascularization. The flap was then carefully transferred to the wounded area and sutured appropriately. A skin graft harvested from the ipsilateral femoral region was used to cover the donor site. Discussion: This case demonstrates the efficacy of the medial plantar artery flap as a local flap option for heel defect coverage. It is a relatively easy-to-perform procedure that provides a strong and thin skin flap. Moreover, it offers a favorable cosmetic outcome for the patient, as the surgical scar can be be relatively easy to hide with footwear. However, limitations of the medial plantar artery flap include its size and depth constraints, as well as loss of vascularization from a medial plantar artery on the plantar region. Conclusion: The medial plantar artery flap is a feasible option as a local flap for the heel region. It is relatively easy to perform, provides a strong thin skin flap, and can results in a preferable cosmetic outcome.